2005
DOI: 10.1523/jneurosci.4075-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neurokininergic Mechanism within the Lateral Crescent Nucleus of the Parabrachial Complex Participates in the Heart-Rate Response to Nociception

Abstract: We wanted to ascertain whether the lateral parabrachial nucleus was involved in mediating the heart-rate response evoked during stimulation of somatic nociceptors. Reversible inactivation of the lateral parabrachial nucleus, using a GABA A agonist, reduced the reflex tachycardia evoked during noxious (mechanical) stimulation of the forelimb by ϳ50%. The same effect was observed after blockade of neurokinin 1 receptors within the lateral parabrachial nucleus, indicating a possible involvement for substance P as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Recently, it was reported that certain respiratory rhythmic neurons in KF responded to cutaneous noxious stimuli and that the resulting respiratory enhancement was attenuated by bilateral inhibition of the parabrachial complex (Jiang et al, 2004). In addition, neurons in the lateral parabrachial nucleus were found to mediate the nociceptic cardiac response (Boscan et al, 2005). These physiologic observations combined with the present anatomic evidence strongly suggest that pneumotaxic neurons are capable of integrating nociceptive and respiratory-related information to coordinate respiratory movement with defensive somatic response.…”
Section: Pneumotaxic Neurons Integrate Pain And/or Musculoskeletal Insupporting
confidence: 65%
“…Recently, it was reported that certain respiratory rhythmic neurons in KF responded to cutaneous noxious stimuli and that the resulting respiratory enhancement was attenuated by bilateral inhibition of the parabrachial complex (Jiang et al, 2004). In addition, neurons in the lateral parabrachial nucleus were found to mediate the nociceptic cardiac response (Boscan et al, 2005). These physiologic observations combined with the present anatomic evidence strongly suggest that pneumotaxic neurons are capable of integrating nociceptive and respiratory-related information to coordinate respiratory movement with defensive somatic response.…”
Section: Pneumotaxic Neurons Integrate Pain And/or Musculoskeletal Insupporting
confidence: 65%
“…One interpretation is that forebrain induced pressor and respiratory responses are mediated by descending projections to rostral PBN. This notion gains support from experiments showing that cardiovascular and/or respiratory responses produced by electrical or chemical stimulation of the CeA, IC, posterior portion of the anterior hypothalamus, dorsal periaqueductal gray and somatic nociceptors were reduced or completely blocked following inhibition of rostral medial and lateral PBN subnuclei (az-Casares et al 2009; Boscan et al 2005; Hayward 2007; Saleh and Connell 2003). Interestingly, the number of LH, CeA, dBNST and IC neurons retrogradely labeled in the present study did not differ as a function of PBN injection site (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…We had some difficulty distinguishing the “lateral crescent” from the central subnucleus of the lateral parabrachial complex as originally defined (Fulwiler and Saper, 1984). Chemical stimulation of this general region of the parabrachial complex (presumably central and lateral crescent nuclei) causes hyperpnea and raises blood pressure and heart rate (Chamberlin and Saper, 1992; Chamberlin, 2004; Boscan et al, 2005). Such responses are also typically elicited by stimulation of central chemoreceptors and could plausibly also be elicited by the excitatory input from the RTN-Phox2b neurons to the lateral parabrachial region.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral crescent and neighboring lateral parabrachial subnuclei also receive input from the C1 neurons of the ventrolateral medulla and from neurons located within the superficial laminae of the spinal cord that relay nociceptive stimuli (Boscan et al, 2005; Card et al, 2006). This convergence of inputs suggests that the lateral crescent or a nearby parabrachial region could be contributing to the arousal or alerting responses caused by a variety of intero- or extero-nociceptive inputs that converge on this region, including hypoxia and hypercapnia (Phillipson et al, 1977; Bowes et al, 1981).…”
Section: Discussionmentioning
confidence: 99%